Kontribusi Sarana Prasarana Pendidikan, Kondisi Lingkungan, Dan Kedisiplinan Kerja Terhadap Kinerja Guru SD Di UPTD Pendidikan Kecamatan Brati Tahun 2015/2016 - Kristiawanto, Kristiawanto; , Prof. Dr. Sutama, M.Pd; , Dr.Suyatmini,SE.,M.Si (2016)
The purpose of this research in general is to examine the contribution of education infrastructure, environmental conditions, and work discipline teacher performance UPTD Pendidikan Kecamatan Brati year 2015/2016 both simultaneously and partially. While the purpose of this research in particular is (1) Testing the contribution of infrastructure of education on the performance of primary school teachers in UPTD District of Brati, (2) Testing the contribution of environmental conditions on the performance of primary school teachers in UPTD Pendidikan Kecamatan Brati, (3) Testing contributions work discipline the performance of elementary school teachers in UPTD Pendidikan Kecamatan Brati. This research is a quantitative research. This study was conducted on 128 respondents in the sample with proportional random sampling technique. The technique of collecting data using questionnaires. Data were analyzed using multiple linear regression analysis, test the accuracy of the model, test the accuracy of parameter estimators (t test), donations predictors and classical assumption. The results of this study stated that: 1) the infrastructure of education, the environment and simultaneously work discipline has contributed to the performance of elementary school teachers in UPTD Pendidikan Kecamatan Brati with α 5% is a significant level of value 1,657 0,000 <0,05 and the effective contribution of 74, 68%. 2) Means of education infrastructure showed a significant influence on the performance of teachers with sig 0.000 <0.05 and the effective contribution of 25.93%. 3) Environmental conditions showed no significant effect on the performance of teachers with sig 0.000 <0.05 and the effective contribution of 11:03%. 4) Discipline work shows significant effects on the performance of teachers with sig 0.000 <0.05 and the effective contribution of 37.72%. 5) The independent variable a contribution of 84.4% of the performance of teachers and 15.6% are influenced by other factors not discussed in this study. So education infrastructure, environmental conditions and work discipline simultaneously significant and positive impact on teacher performance. Keywords: infrastructure, environment, discipline, teacher performance